A Comprehensive Survey of Soft Wheat Grain Quality in U.S. Germplasm. Issue 1 (9th January 2013) - Kiszonas, Alecia M.; Fuerst, E. Patrick; Morris, Craig F.
ABSTRACT: Wheat ( Triticum aestivum L.) quality is dependent upon both genetic and environmental factors, which work in concert to produce specific grain, milling, flour, and baking characteristics. This study surveyed all of the 132 soft wheat varieties (cultivars and advanced breeding lines) grown in the U.S. regional nursery system, which encompassed the three main soft wheat producing regions of the United States (eastern and southern soft red winter and western soft white). The quality parameters included test weight, kernel hardness, weight, and diameter, wheat and flour protein, polyphenol oxidase, break flour yield, flour yield, flour ash, milling score, flour swelling volume, flour SDS sedimentation volume, solvent retention capacity (SRC) for water, sodium carbonate, sucrose, and lactic acid, Rapid Visco Analyzer peak pasting viscosity, and cookie diameter. High levels of variation were observed among varieties, regions, and specific environments, with environment being in general a much greater source of variation than varieties. Variety was observed to have a relatively stronger influence on wheat quality in the western nurseries, compared with the eastern and southern regions, where location effects had a stronger impact on overall wheat quality. The greater influence of variety was particularly notable for kernel hardness in the western nurseries. Kernel hardness also varied considerably as a result of environment. For the two soft red winter wheat nurseries, the western U.S. environment produced substantially harder kernels (37–40) compared with the same varieties grown in eastern U.S. locations (15–20). Intertrait quality relationships were observed to be unique to the specific nursery and germplasm in which they were studied, and these relationships were not consistent across nurseries. Nevertheless, on average, soft wheat quality was fairly similar across the United States, indicating that breeding and testing models have been successful in achieving a relatively uniform target for quality. However, many traits showed high levels of variability among varieties, suggesting that a greater level of selection for end‐use quality would benefit end users by increasing consistency and reducing variability. The often large role of environment (location) in quality indicates that end users must be assiduous in their origination and grain procurement. Clearly, "nursery mean" quality does not reflect the potential that can be obtained, as reflected by a few exceptional soft wheat varieties.